Can transplanting enhance mobile marine invertebrates in ecologically engineered rock pools?. (October 2018) - Morris, Rebecca L.; Martinez, Aline S.; Firth, Louise B.; Coleman, Ross A.
Abstract: The field of eco-engineering has burgeoned in recent years in response to the proliferation of artificial structures. Adding water-retaining features to seawalls has been successful in increasing biodiversity relative to the surrounding structure. Artificial rock pools may not, however, completely mimic natural rock pools. Here, we compared natural colonisation, through dispersal and recruitment, of intertidal mobile species to water-retaining flowerpots on seawalls with that into rock pools. This represents the more usual 'passive' approach to eco-engineering where features are built to enhance biodiversity and are allowed to colonise naturally, as opposed to seeding or transplanting organisms to features. While flowerpots supported some mobile species not found on the seawall, other species common on natural shores did not recruit to flowerpots. Thus, in a second experiment we tested the effectiveness of an 'active' approach through transplanting mobile organisms to flowerpots to expedite the colonisation process. For the species examined, however, most individuals did not stay in the flowerpots for more than 24 h after being transplanted. Further understanding of the processes (e.g. dispersal distances, recruitment) influencing colonisation of eco-engineered habitats is needed to effectively inform management of marine infrastructure, particularly for projects targeted at restoration rather than enhancement. Highlights: Mobile invertebrates are ubiquitous in natural rock pools. Water-retaining flowerpots were added to seawalls to enhance biodiversity. Some mobile species found in rock pools do not colonise or recruit to flowerpots. Seeding was tested as an active approach to increase flowerpot colonisation. Most individuals transplanted did not stay in the flowerpots for more than 24 h.